Sukatani Platform Sahabat Petani (Current Research in Education: Conference Series Journal, 2023)
Indonesia is known as an agricultural country that has extensive agricultural land, with most of the population working in agriculture. With these abundant resources, they are used by the mafia and rogue dealers to strangle farmers. However, farmers also need their services to distribute the farmers' crops to reach consumers. Purpose of this research is to develop a Sukatani information system. Sukatani itself is can be a solution to the problems felt by farmers and consumers, with a better distribution system by maximizing the potential of information systems that can cut rogue dealers to consumers directly, can sell on market or can use help of mobile vegetable vendors to maximize market reach, with prices adjusted to the supply owned in an area, supported by savings and loan cooperatives, information and education media. This research method uses the System Development Life Cycle (SDLC). The results of this study are only first 2 stages based on the 5 stages. Requirement analysis stage using interviews with 7 farmers, and 2 middlemen spread across Indonesia, up to stage 2 system and software design. The results of this study resulted in the DFD process up to level 2, user flow, and interface design from Sukatani.